Effective boundary condition method and Rayleigh waves in orthotropic half-spaces coated by a thin layer with sliding contact - Vinh, P.C.; Anh, V.T.N. (Archives of Mechanics, 2015)
This paper studies the propagation of Rayleigh waves in an orthotropic elastic half-space coated by a thin orthotropic elastic layer. The half-space and the layer are assumed to be either compressible or incompressible and they are in sliding contact with each other. The main aim of the paper is to establish approximate secular equations of the wave for all (four) possibilities of a compressible or incompressible half-space covered with a compressible or incompressible thin layer, except the case of a compressible half-space coated by a compressible layer that has been considered [19]. In order to do that, the effective boundary condition method is employed and the approximate third-order secular equations regarding the dimensionless thickness of the layer are derived. It is shown that these approximate secular equations have a high accuracy. Based on the obtained secular equations, the effect of incompressibility on the Raleigh wave propagation is considered through some numerical examples. It is shown that incompressibility strongly affects the Raleigh wave velocity and the effect becomes stronger when the coating is incompressible.